Determinants of job satisfaction for salaried and self-employed professionals in Finland - Hytti U; Kautonen T; Akola E (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
This article contributes to our knowledge of the determinants of job satisfaction by analysing the effects of employment status (self-employed or salaried employee) and work characteristics (autonomy, variety, task identity, task significance and feedback) on job satisfaction in a sample of 2327 Finnish professionals. The results of the analysis show that although the self-employed professionals are significantly more satisfied with their jobs than their salaried counterparts in Finland, employment status as such does not explain job satisfaction when the five work characteristics are added to the structural model. Furthermore, the analysis finds that task significance, variety and autonomy have similar effects on the level of job satisfaction among both employees and self-employed individuals, while feedback has a weaker effect when the individual is self-employed and task identity does not affect job satisfaction in either group. Overall, the study points to the need to develop jobs that are high in autonomy, variety and task significance for professionals in order to enhance job satisfaction.